USING CHLORHEXIDINE 0.2% AND POVIDONE IODINE 1% AS ORAL DECONTAMINATION TO COLONIZATION Staphylococcus aureus AT POST OPERATIVE PATIENTS WITH GENERAL ANESTHESIA - Rondhianto; Wantiyah; Febrian Maulana Putra (Program Studi Ilmu Keperawatan Universitas Jember, 2016)
Post-operative patients with general anesthesia are highly risk of mucus hypersecretion and respiratory distress as the effect of anesthesia caused by secretions accumulation in oropharynx. One of nursing interventions to decrease accumulation of mucus is by oral hygiene. The purpose of this study was to determine the differences of using chlorhexidine 0.2% and povidone iodine 1% as oral decontamination to the colonization of Staphylococcus aureus of post-operative patients in mawar ward at Dr. Abdoer Rahem Hospital Situbondo. This study was a quasy experimental research with non-equivalent control group design. The samples in this study were 20 samples divided into two groups 10 as the treatment group was given chlorhexidine 0.2% and 10 as the control group was given povidone iodine 1%. Data were analyzed by using Mann-Whitney. The result of Mann-Whitney test showed p value (0.490) > alpha (0.05). However, there was no difference between chlorhexidine 0.2% and povidone iodine 1% as oral decontamination for colonization of Staphylococcus aureus of post-operative patients in mawar ward at Dr. Abdoer Rahem Hospital Situbondo. The conclusion is chlorhexidine 0.2% and povidone iodine 1% can be used as oral decontamination for post-operative patients with general anesthesia.